Departmental PLCs in secondary schools: the importance of transformational leadership, teacher autonomy, and teachers' self-efficacy - Valckx, Jasja; Vanderlinde, R.; Devos, G. (Educational studies, 2020)
Professional learning communities (PLCs) are considered ideal contexts for teachers' professional development and school improvement. Therefore, it is necessary to explore the interplay between PLC characteristics (i.e. collective responsibility, reflective dialogue, and deprivatized practice) in secondary school departments, and understand what variables (i.e. transformational leadership by the principal, teacher autonomy, and teachers' self-efficacy) stimulate these PLC characteristics. Data was collected from 324 Mathematics, French, and General Studies teachers in 80 departments of 33 Flemish secondary schools. The results of a path analysis show that teachers' collective responsibility and self-efficacy are positively related to their reflective dialogue. Furthermore, the relationship between transformational leadership by the principal and reflective dialogue is fully mediated by collective responsibility. Finally, the relationship between teacher autonomy and reflective dialogue is fully mediated by teachers' self-efficacy.